(untitled) (Bangladesh Journal of Urology, 2020)
Objectives: To compare the efficacy of intraprostatic infiltration of lidocain injection and periprostatic nerve block for pain free TRUS guided prostate biopsies. Methods: A hospital based prospective experimental study was conducted in the Department of Urology of Dhaka Medical College Hospital, Dhaka from July 2007 to June 2009 to compare the different anesthesia technique for TRUS guided prostate biopsy for the detection of carcinoma prostate. All male patients aged over 55 years having lower urinary tract symptoms (LUTS) attending to urology OPD as well as in patient department were evaluated by history, physical examination including D/R/E and necessary investigations to identify the potential candidates for prostate biopsy and potential participants were counselled for prostate biopsy. Before taking biopsy patients were again judged by selection and exclusion criteria. Overall general examination as well as examination of urinary system and anorectal region was done. DRE was done to see the size, consistency and nodularity of prostate prior to biopsy. Who fulfilled the selection criteria included in this study in out patient basis or admitted in the urology ward and numbered chronologically, odd numbers for group-I includes periprostatic nerve block and even numbers for group-II includes intraprostatic infiltration of lidocain injection. They underwent 10 core prostate biopsy (standard 6 plus lateral 4 core) and hypoechoic lesion directed biopsy to see the unique cancer detection rate in each lobe. Data were analyzed using SPSS (Statistical package for social science) software program. The test of significance were chi-square, student t test, Fisher exact test, Mann Whitney test. Probability value (P Value<0.05) was considered significant. Results: Intensity of pain using visual analogue scale (VAS) demonstrates that the mean pain intensity during probe insertion was significantly less in Group-I than that in Group-II (5.8 ± 1.3 vs. 6.7 ± 1.3, p = 0.007). The mean pain intensity during anesthesia was also significantly less in the former group compared to the latter group (4.5 ± 1.2 vs. 5.1 ± 1.1, p = 0.036). Then the pain intensity of both the groups decreased, but the decrease was significantly faster and steeper in Group-II than in Group-I (p = 0.001). The pain intensity of Group-II 30 minutes after biopsy further decreased to 1.9 cm on visual analogue scale, while the pain intensity of Group-I increased from 4.1 cm during biopsy to 4.4 cm 30 minutes after biopsy (p < 0.001) . Results of the study revealed that -intraprostatic administration of local anesthesia significantly decreases the pain associated with prostate biopsy compared with conventional periprostatic nerve block. Conclusions: Intraprostatic administration of local anesthesia significantly decreases the pain associated with prostate biopsy compared with periprostatic nerve block. It is a simple, safe and rapid technique that should be considered in all patients undergoing transrectal ultrasound guided prostate biopsy Bangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.87-93